Micro-scale Biodrying of Municipal Waste for Refuse Derived Fuel (RDF) Production - Berlian Sitorus; Seno Darmawan Panjaitan; Yopa Eka Prawatya; Wivina Diah Ivontianti; Muhammad Ivanto; Septami Setiawati; Riysan Octy Shailindry; Maria Yeni Wahyuningsih; Benedikta Arni (Reaktor, 2026)
Municipal solid waste (MSW) continues to increase worldwide, driven by rapid urbanization and population growth. This study explores the biodrying process as a sustainable approach to convert MSW into refuse-derived fuel (RDF), offering an alternative renewable energy source. Biodrying, a biological phase within the mechanical–biological treatment (MBT) system, removes moisture through microbial activity supported by controlled aeration. The experiment evaluated different aeration rates (0, 6, and 8 L/min) and residence times (7, 14, and 21 days) to assess their impact on the quality of RDF. Higher aeration enhanced drying performance and increased the calorific value up to 4260 kcal/kg, while longer residence time improved moisture reduction and heating efficiency. However, the non-aerated condition (0 L/min) demonstrated greater process stability and energy efficiency, achieving 4044 kcal/kg with lower operational demand. Thus, while forced aeration improved RDF quality, the passive (non-aerated) setup represented the most energy-efficient operating condition. The optimal configuration, 0 L/min aeration and 7-day residence time, produced RDF with 8.2% moisture, 1.0% ash, 76.5% volatile matter, and 14.3% fixed carbon. The resulting RDF complied with SNI 8966:2021 Class II solid fuel standards, equivalent to low-grade brown coal (<7000 cal/g). These findings indicate that passive biodrying without forced aeration can effectively enhance RDF quality with minimal energy input. The process demonstrates a simple, low-cost, and energy-efficient strategy for transforming mixed municipal waste into renewable solid fuel, supporting the circular economy and sustainable energy goals.